(untitled) (INNOVATIVE ECONOMY, 2023)
Fedoryshyna L.M., Kononiuk O.O., Kononiuk I.A. RESOURCE POTENTIAL OF THE TERRITORIAL COMMUNITY: ESSENCE, COMPONENT ELEMENTS AND FACTORS OF FORMATION Purpose. The purpose of the article is to research the essence of the resource potential of the territorial community, determination of its structure and outline of the factors influencing its formation. Methodology of research. The following research methods are used to achieve such purpose: analytical, monographic, abstract and logical - for consideration of the essence of the concept of “resource potential” at the macro-, meso-, and micro-levels and the selection of the concept of “resource potential of the territorial community”; inductions, deductions, structural analysis - for determination the components of the resource potential of the territorial community and factors affecting its formation; tabular, graphic - for a visual presentation of systematized material to determine the essence of the concept of “resource potential” and components of resource potential. Findings. It has been studied essence of the concept of “resource potential” at the macro-, meso-, and micro-levels, and summarized while the existing approaches in the scientific literature regarding its interpretation. It is divided concept of “resource potential of the territorial community” into meso-level. It is defined and characterized the components of the resource potential of the community (natural resources, material and technical, financial, demographic (labour), investment, recreation); it is indicated the importance of research and study of each of them for the development of the community. The main factors of formation of resource potential of the community are outlined. Originality. There was further development of the study of the essence of the concept of “resource potential of the territorial community”, which in the author’s interpretation should be considered as a set of all available resources that are available and necessary for the implementation of economic activity, and hidden opportunities that can be used at a certain time and under certain circumstances under the leadership of the local self-government, which will guarantee the provision of quality services and the satisfaction of the needs of residents, will ensure the competitiveness, social and economic stability of the community. Practical value. The results of the research can be the basis for further research into the regarding the effective use of the components of the resource potential of the territorial community and the development of methods for their assessment.